Intermedin Inhibits the Ox-LDL–Induced Inflammation in RAW264.7 Cells by Affecting Fatty Acid–Binding Protein 4 Through the PKA Pathway - Liu, Kai; Shi, Rufeng; Wang, Si; Liu, Qi; Zhang, Hengyu; Chen, Xiaoping (Frontiers in Pharmacology, 2021)
Objectives: Macrophages stimulated by oxidized low-density lipoprotein (ox-LDL) play an important role in the occurrence and progression of atherosclerosis (AS). Fatty acid-binding protein 4 (FABP4), mainly existing in macrophages and adipocytes, can influence lipid metabolism and inflammation regulated by macrophages. Herein, we first established the connection between Intermedin (IMD: a new peptide that has versatile biological activities in the cardiovascular) and FABP4 and then investigated the influence of IMD on ox-LDL-induced changes in RAW264.7 macrophages line. Methods: Bioinformatic analysis, such as gene ontology enrichment and protein-protein interactions were performed. For ox-LDL stimulated assays, the RAW264.7 was first pretreated with Intermedin and then exposed to ox-LDL. To explore the cell signaling pathways of Intermedin on inflammatory inhibition, main signaling molecules were tested and then cells were co-incubated with relevant inhibitors, and then exposed/not exposed to Intermedin. Finally, cells were treated with ox-LDL. Protein and gene expression of FABP4, IL-6, and TNF- were quantified by WB/ELISA and RT-qPCR. Results: In the ox-LDL stimulated assays, exposure of the RAW264.7 macrophages line to ox-LDL reduced cell viability and increased the expression of FABP4, as well as the release of IL-6 and TNF-(all p<0.05). On the other hand, IMD prevented ox-LDL induced cell toxicity, FABP4 expression, and the inflammatory level in RAW264.7 (all p<0.05) in a dose-dependent manner. The inhibition of FABP4 and the anti-inflammatory effect of IMD were partially suppressed by the PKA inhibitor H-89. Conclusions: Intermedin can prevent ox-LDL-induced macrophage inflammation by inhibiting FABP4, whose signaling might partially occur via the PKA pathway.